Micro-costing diabetic eye screening: estimation of personal expense, attendance and health care resource use - James, Marilyn; Sampson, Christopher James; van Eker, D.; Harding, S.P. (Witchtig Publishing, 2016)
Design of study Microcosting study with collection and analysis of primary and secondary data on resource use and costs.